Analisis Isi Kuantitatif Tentang Kekerasan Verbal dalam Tayangan Adegan Film Parasite Tahun 2019 - Lulu Chamdliyah; Siti Hadiyatul Hasanah; Viola Sendy Karolina; Ananda Dwita Yuniar (Persepsi: Communication Journal, 2022)
AbstractThe film Parasite by Bong Joon Hoo is a film that tells about the conflict that occurs between a rich family and a poor family that shows social inequality, so that this film is judged to use a lot of verbal violence. This quantitative content analysis research was carried out with the hope of being able to describe the frequency of verbal violence in Parasite Film and educate readers about the elements of verbal violence that occur in Parasite Film. The method used in this study is a descriptive quantitative method. The unit of analysis of this research is all scenes of verbal violence in the film Parasite. There are two sources of data in this research, namely primary data sources through the film Parasite and secondary data sources from documentation and literature studies. The population of this research is all scenes in the film Parasite which has a duration of 2 hours 12 minutes. Determination of the sample of this study using purposive sampling technique. The results obtained from this study are the frequency of verbal violence scenes in Parasite Film in 2019 found 44 times verbal violence with insulting indicators 17 times with a percentage of 39%, said rudely 7 times with a percentage of 16%, shouted 9 times with a percentage of 20 %, threatened 4 times with a percentage of 9%, and scolded 7 times with a percentage of 16%. Thus, it can be concluded that verbal violence that is mostly done is insulting and yelling.Keywords: Content Analysis, Verbal Violence, Parasite Movie